Extrachromosomal Circular DNA MIRECD Enhances Necroptosis and Predicts Prognosis of Myocardial Infarction - Yiheng Zhao; Yujia Zhou; Shuchen Zhang; Boyang Xiang; Xiang Zhou (Research)
Recent researches have revealed the potential utility of extrachromosomal circular DNAs (eccDNAs) as biomarkers in various diseases. However, the association between plasma eccDNAs and myocardial infarction (MI) remains unclear. In this study, we extracted plasma eccDNA from blood samples of individuals with acute MI and conducted Circle-Seq. We identified an MI-related eccDNA (MIRECD) with high expression levels in the plasma of patients with MI. Sanger sequencing validated its loop construction and sequence. Mechanistically, MIRECD could aggravate necroptosis via regulating the expression of mixed-lineage-kinase-domain-like pseudokinase (MLKL). Kaplan–Meier analysis demonstrated that the incidences of major adverse cardiac events (MACEs) and cardiovascular mortality were higher in individuals with elevated MIRECD levels. Univariate and multivariate Cox regression analyses indicated that MIRECD independently predicted the occurrence of MACEs in patients with MI. The addition of MIRECD enhanced the discrimination and reclassification ability compared with conventional risk factors. In conclusion, our study identified a novel eccDNA, MIRECD, which might regulate myocardial necroptosis through MLKL. MIRECD has the potential to serve as a reliable indicator for predicting the prognosis and stratifying the risk of MI.